Non-refoulement under the European Convention on Human Rights and the UN Convention against Torture: The Assessment of Individual Complaints by the European Court of Human Rights under Article 3 ECHR and the United Nations Committee against Torture under Article 3 CAT - De Weck, Fanny (International Refugee Law Series, 2017)
This book offers a comprehensive analysis and comparison of the practice and case law of the European Court of Human Rights and the UN Committee against Torture in the assessment of individual complaints concerning the principle of non-refoulement.